Differential Reinforcement of Other Behaviors to Treat Challenging Behaviors Among Children With Autism: A Systematic and Quality Review. Issue 4 (July 2018) - Weston, Regan; Hodges, Abby; Davis, Tonya N.
This review summarizes the literature regarding differential reinforcement of other behaviors (DRO) to treat challenging behavior among children with autism spectrum disorder (ASD) and determines the quality of studies among the current literature according to the 2014 Council for Exceptional Children (CEC): Standards for Evidence-Based Practices in Special Education . Studies that focused on the use of DRO in the treatment of challenging behavior for individuals with ASD were included for systematic analysis. Forty-five studies were identified for inclusion in this review and were evaluated using the eight quality indicators described by the CEC. To the authors' knowledge, this is the only systematic review of the literature that evaluates DRO as an intervention for individuals diagnosed with ASD. Principle findings, practical recommendations, and areas of future research are discussed.